PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO AMANDA BROWNIES - Evinda Deviana Br Situmorang; Robinhot Gultom; Kristanty Nadapdap; Mislan Sihite (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2019)
This study aims to determine the influence of service quality and product quality on consumer purchase decision at Amanda Brownies Store in Medan. Thepopulation of this study was taken from the number of consumers for 6 month totalling 1,509 or 252 consumers in a month. The number of samples taken in this study was 155 consumers. The data collection methods in this study used questionnaires among 155 consumers of Amanda Brownies Store in Medan. The data analysis method used was Multiple Linear Regression method. The partial testing analysis shows that service quality and product quality have a significant effect on consumer purchase decision. Furthermore, the simultaneous test results showed that the service quality variable and product quality variable significantly influence the consumer purchase decision. The Adjusted R Square is 0.316 or 31.6%. This means that 31.6% of consumer purchase decision is influenced by both independent variables, while the remaining 68.4% of customer purchase decision is influenced by other variables-not examined in this study.